ANALISA PENGAKUAN PENDAPATAN PROYEK DAN BIAYA PROYEK SERTA PPH PASAL 4 AYAT 2 PADA LAPORAN KEUANGAN PT ADHI KARYA (PERSERO) Tbk. PROYEK RS SANTO BORROMEUS GEDUNG ELIZABETH - Iwan Irdiawan; Herry Winarto (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2020)
The research of this research is to know the treatment of income and expenses as well as income tax article 4 paragraph 2 in PT Adhi Karya (Persero) Tbk. In accordance with PSAK No. 34. This research method uses qualitative research, namely the results of research in the form of descriptive data that can be accounted for. According to PSAK No. 34, contract revenue related to construction contracts should be recognized as income with due regard to the stage of completion of contract activity at the balance sheet date. PT Adhi Karya (Persero) Tbk determines revenue recognition using the Completion Percentage Method. The accounting bookkeeping method is on an accrual basis, namely revenue is recorded or recorded at the time the transaction is made. The recording of Income Tax Article 4 paragraph 2 can only be reduced after the company receives proof of withholding from the owner.